Control of amylase production and growth characteristics of Aspergillus ochraceus - Nahas, Ely [UNESP]; Waldemarin, Mirela M. (My University, 2002)
The growth and the extracellular amylase production by Aspergillus ochraceus were studied in a stationary culture medium. Maximum growth rate of this fungus was found after 5 days of incubation at 30° C, but maximum amylase production was obtained after 2 days. The highest amylase production were attained with lactose, maltose, xylose and starch as carbon sources. The extracellular amylase production and mycelial growth were influenced by the concentration of starch. Other carbohydrates supported growth but did not induce amylase synthesis and glucose repressed it, indicating catabolite repression in this microorganism. The presence of both mechanisms of induction and repression suggests that at least these multiple forms of regulation are present in A. ochraceus. Of the nitrogen sources tested, casaminoacids, ammonium nitrate and sodium nitrate stimulated the highest yield of amylase. Optimal amylase production was obtained at pH 5.0, but enzyme activity was found only in the 4.0-6.0 pH range. These results were probably due to the inhibitory effect of NH 4 +-N in the culture medium.
Keywords: α-amylase; Aspergillus ochraceus; Carbon source; Nitrogen source; ammonium nitrate; amylase; carbohydrate; carbon; casamino acid; glucose; lactose; maltose; nitrogen; sodium nitrite; starch; xylose; concentration (parameters); enzyme activity; enzyme induction; enzyme synthesis; fungus culture; fungus growth; growth rate; mycelial growth; nonhuman; pH; Amylases; Carbohydrate Metabolism; Carbohydrates; Carbon; Caseins; Culture Media; Enzyme Induction; Fungal Proteins; Glucose; Nitrates; Nitrites; Nitrogen; Starch; Temperature; Aspergillus; Fungi